Despre frumos, fantasme erotice și complexe în „Elogiu mamei vitrege”, de Mario Vargas Llosa [About beauty, erotic phantasms and complexes in “Eulogy to the stepmother” by Mario Vargas Llosa] - Liliana Danciu (Incursiuni în imaginar)
A strong human and artistic personality, Mario Vargas Llosa has often imposed his will, desires and artistic vues. In everyday life, he scandalized both public opinion and family by transgressing boundaries. In his literary creation, he abandoned all hypocrisy, approached uncomfortable aspects of everyday life, such as incest and the love triangle, the phenomenon of violent imposition of government, even if democratic, against the will of the many. In his essay The Perpetual Orgy: Flaubert and Madame Bovary, Llosa confesses that man's vocation, his own implicitly, is to break the rules, even if that way of acting is called Evil. Because the taboos existing in Emma Bovary’s times remain and they need to be surpassed. Beauty (from Plato to Thomas Mann filtered by Nietzsche's philosophy) and its interference with erotic fantasies (dreamlike and artistic ones) experienced by the heroes of the novel Eulogy to the stepmother represent the main challenge of this paper. This challenge leads towards the analysis of the psychological complexes manifested by Don Rigoberto (Kandaules), Dona Lucrecia (Venusian) and the prepubert Foncin (the tendency to castrate the father and the double complex manifested towards the mother (Oedipal and Don Juan). The libido is understood in the Jungian sense, as a psychic energy, which, related to the final phantom images projected by the psyche, reflects the uncontrollable desires and impulses of individuals. In Eulogy to the stepmother, the adult couple deals with sexual desires, while the kid is guided by a conscious desire towards vengeance and humiliation, then falls under the influence of the libido understood as sexuality. The rich mythological references help us in this psychoanalytic and mythocritical approach.